Dark matter distribution in X-ray luminous galaxy clusters with Emergent Gravity. (11th May 2017) - Ettori, S.; Ghirardini, V.; Eckert, D.; Dubath, F.; Pointecouteau, E.
Abstract: We present the radial distribution of the dark matter in two massive, X-ray luminous galaxy clusters, Abell 2142 and Abell 2319, and compare it with the quantity predicted as apparent manifestation of the baryonic mass in the context of the 'Emergent Gravity' scenario, recently suggested from Verlinde. Thanks to the observational strategy of the XMM–Newton Cluster Outskirt Programme (X-COP), using the X-ray emission mapped with XMM–Newton and the Sunyaev–Zel'dovich signal in the Planck survey, we recover the gas density, temperature and thermal pressure profiles up to ∼ R 200, allowing us to constrain at an unprecedented level the total mass through the hydrostatic equilibrium equation. We show that, also including systematic uncertainties related to the X-ray-based mass modelling, the apparent 'dark' matter shows a radial profile that has a shape different from the traditional dark matter distribution, with larger discrepancies (by a factor of 2–3) in the inner ( r  < 200 kpc) cluster's regions and a remarkable agreement only across R 500 .